2014
DOI: 10.5812/numonthly.19411
|View full text |Cite
|
Sign up to set email alerts
|

Association of Diet With Prostate Specific Antigen and Prostate Volume

Abstract: Background:Prostate is an important male reproductive system gland and its disorders can affect men's quality of life and health. Prostatitis, benign prostatic hyperplasia (BPH), and prostate adenocarcinoma are major disorders that can be found in all men in different ages.Objectives:The aim of this study was to investigate the association of diet with serum prostate specific antigen (PSA) level as well as prostate volume.Patients and Methods:In this cross-sectional study, 950 men older than 40 years of age wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
5
1
Order By: Relevance
“…Previous studies by Shirazi and colleaques also reported a significant correlation between age and serum PSA level as well as with prostate volume [18]. The authors further stated that a significant correlation existed between serum PSA level and prostate volume and therefore acute urinary retention [18,27]. These findings are conflicting considering the reports of Bhagya et al [28].…”
Section: Pearson's Correlation Study For Bph With or Without Renal Imcontrasting
confidence: 56%
See 2 more Smart Citations
“…Previous studies by Shirazi and colleaques also reported a significant correlation between age and serum PSA level as well as with prostate volume [18]. The authors further stated that a significant correlation existed between serum PSA level and prostate volume and therefore acute urinary retention [18,27]. These findings are conflicting considering the reports of Bhagya et al [28].…”
Section: Pearson's Correlation Study For Bph With or Without Renal Imcontrasting
confidence: 56%
“…Serum PSA trends over time (PSA velocity), measurement of free versus complexed PSA, and PSA density may help to improve the specificity of PSA testing in men with BPH. Previous studies by Shirazi and colleaques also reported a significant correlation between age and serum PSA level as well as with prostate volume [18]. The authors further stated that a significant correlation existed between serum PSA level and prostate volume and therefore acute urinary retention [18,27].…”
Section: Pearson's Correlation Study For Bph With or Without Renal Immentioning
confidence: 80%
See 1 more Smart Citation
“… 17 Also, the adverse effects of BPH are relatively apparent in men >50 years of age. 18 19 According to the results of this study, among Chinese adults with LUTS/BPH, PV and LUTS deteriorated as age increased. Indeed, Shi et al 18 and Chokkalingam et al 17 selected age ≥50 years as an inclusion criterion for studying BPH.…”
Section: Discussionmentioning
confidence: 76%
“…According to Zhang et al , 26 the frequency of animal protein intake is positively correlated with PV. However, according to Shirazi et al , 19 no relationship was detected between dietary patterns and PV. Second, the relationship between diet and BPH is mixed.…”
Section: Discussionmentioning
confidence: 95%